Application of the adjoint approach to optimise the initial conditions of a turbidity current with the AdjointTurbidity 1.0 model - parkinson,SD; Funke,SW; Hill,J; Piggott,MD; Allison,PA (Geoscientific Model Development, 2017)
Turbidity currents are one of the main drivers ofsediment transport from the continental shelf to the deepocean. The resulting sediment deposits can reach hundredsof kilometres into the ocean. Computer models that simulateturbidity currents and the resulting sediment deposit can helpus to understand their general behaviour. However, in orderto recreate real-world scenarios, the challenge is to find theturbidity current parameters that reproduce the observationsof sediment deposits.This paper demonstrates a solution to the inverse sedimenttransportation problem: for a known sedimentary deposit, thedeveloped model reconstructs details about the turbidity cur-rent that produced the deposit. The reconstruction is con-strained here by a shallow water sediment-laden density cur-rent model, which is discretised by the finite-element methodand an adaptive time-stepping scheme. The model is differ-entiated using the adjoint approach, and an efficient gradient-based optimisation method is applied to identify the turbidityparameters which minimise the misfit between the modelledand the observed field sediment deposits. The capabilities ofthis approach are demonstrated using measurements taken inthe Miocene Marnoso-arenacea Formation (Italy). We findthat whilst the model cannot match the deposit exactly dueto limitations in the physical processes simulated, it providesvaluable insights into the depositional processes and repre-sents a significant advance in our toolset for interpreting tur-bidity current deposits.